1987
DOI: 10.1073/pnas.84.24.9199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the cell-surface expression of immunoglobulin mu chain without light chain in human B lymphocytes.

Abstract: Four distinct human B-lymphoid cell lines possess the ability to circumvent the mechanism regulating intracellular transport of immunoglobulin protein. These cells do not produce light chains, yet they express ,u heavy chains on the cell surface at comparable levels to B-cell lines that produce native forms of both proteins. The IL-chain mRNA produced in all four cell lines was found to contain an identical deletion of most of the heavy-chain variable (VH) region (75% of the 3' portion), with no apparent alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, the nature of the deletions makes it possible that within these large segments of HN more than one site is available to interact with GRP78-BiP, but these remain to be determined. Naturally occurring deletions of these domains reduce the association with GRP78-BiP and allow the secretion of HC in the absence of light-chain synthesis Pollock et al, 1987). However, these observations should not be necessarily interpreted to suggest that GRP78-BiP is absent from the process of folding of mutant HC because either deletion mutant may continue to contain the other available binding sites.…”
Section: Discussionmentioning
confidence: 70%
“…However, the nature of the deletions makes it possible that within these large segments of HN more than one site is available to interact with GRP78-BiP, but these remain to be determined. Naturally occurring deletions of these domains reduce the association with GRP78-BiP and allow the secretion of HC in the absence of light-chain synthesis Pollock et al, 1987). However, these observations should not be necessarily interpreted to suggest that GRP78-BiP is absent from the process of folding of mutant HC because either deletion mutant may continue to contain the other available binding sites.…”
Section: Discussionmentioning
confidence: 70%
“…Previous workby Hendershot et al (1987) and Pollok et al (1987) has provided strong evidence that the stable retention of newly synthesized Ig heavy chains within the ER is a consequence oftheir association with BiR They have shown that large deletions in either the first constant region domain (CHI) or in the variable region (VH) of Ig heavy chains result in proteins that do not interact with BiP The lack of BiP binding is correlated with secretion of CH, mutants and the surface expression of VH mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The association between X5 and j. heavy chains seems to occur through the CH1 domain of it, as deletions of this domain result in loss of association between /,4 and these polypeptides (43). Based on the conservation ofBiP binding and light chain binding to y2b via associations within the CH1 domain, it seems reasonable to expect that X5, which is structurally similar to a light chain, may also associate with y2b (44)(45)(46)(47) . However, even if y2b can bind X5, a correct signal for B cell maturation may not be created.…”
Section: Y2b In B Cell Developmentmentioning
confidence: 99%